Uji Efek Daun Jati dan Senggani Terhadap Penurunan Suhu Tubuh pada Tikus yang diinduksi Pepton - Seriyani Wulandari; Dhini Andriani; Fhadlyatul Khusna; Mu'tia Aulia Ramadhani; A. Ilmi Alfiani; Nadia Nadia (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This study aims to examine the effect of several types of antipyretics on the immune response and body thermal homeostasis in experimental animals induced by fever. This study was conducted at the Pharmacology and Toxicology Laboratory of Muhammadiyah University of Makassar, using Rattus norvegicus mice as test animals. The study involved five treatment groups, each given a different drug or infusion, namely diclofenac sodium, ibuprofen, farmadol, teak leaf infusion (Tectona grandis), and senggani leaf infusion (Melastoma malabathricum), while NaCMC was used as a negative control. Body temperature measurements were taken at 15, 30, 45, and 60 minutes after treatment to evaluate the effect of antipyretics on body temperature in fever-induced mice. Each treatment group was given a dose according to the related literature, and temperature measurements were carried out using a well-calibrated thermometer. The data obtained were then analyzed using ANOVA to determine any significant differences in body temperature reduction between treatment groups. The results showed that sodium diclofenac provided the highest antipyretic effect, as seen from a significant decrease in body temperature at all measurement times. Ibuprofen also provided a significant antipyretic effect, although not as strong as sodium diclofenac. Meanwhile, teak leaf infusion and senggani leaf infusion showed a decrease in body temperature, but with lower effectiveness compared to synthetic drugs. The group given NaCMC as a negative control did not show a significant decrease in body temperature. These findings indicate that sodium diclofenac is very effective in restoring the body's thermal balance and can be a reference for further research on antipyretic agents, both synthetic and herbal. The implications of this study also emphasize the importance of developing alternative fever therapies, either through more efficient synthetic drugs or through the use of herbal plants that have the potential as natural antipyretics.